(untitled) - Medical Letter, Inc. (New Rochelle, N.Y., 1996)
Contents: Antibacterial drugs, antituberculosis drugs, antiviral drugs, drugs for sexually transmitted diseases, antifungal drugs, antiparasitic drugs,...
Keywords: Drug Interactions,Drug therapy,Pharmacology; Handbooks,Handbooks